2016
DOI: 10.1080/10286020.2016.1194833
|View full text |Cite
|
Sign up to set email alerts
|

Renchangianins F and G: two new sesquiterpenoids from Kadsura renchangiana

Abstract: Phytochemical investigation on the stems of Kadsura renchangiana led to the isolation of two new sesquiterpenoids, renchangianins F and G (1 and 2). Their structures were elucidated by spectroscopic methods, including 2D NMR techniques. The in vitro cytotoxic activities of the isolates were studied against HepG2, A549, and LN229 cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In the last few decades, phytochemical work on the family Schisandraceae has resulted in a seminal contribution to novel structural frameworks for triterpenoidal skeletons [1,2,3,4]. Recently, some promising sesquiterpenes has also been reported from the plants of family Schisandraceae [5,6,7,8,9,10]. In our previous research, we reported the identification of several bioactive lignanoids from the genus kadsura [11] that highlight the immense diversity in the chemical constituents of these plants as well as in their important biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, phytochemical work on the family Schisandraceae has resulted in a seminal contribution to novel structural frameworks for triterpenoidal skeletons [1,2,3,4]. Recently, some promising sesquiterpenes has also been reported from the plants of family Schisandraceae [5,6,7,8,9,10]. In our previous research, we reported the identification of several bioactive lignanoids from the genus kadsura [11] that highlight the immense diversity in the chemical constituents of these plants as well as in their important biological activities.…”
Section: Introductionmentioning
confidence: 99%